Examining Impact of Internal Problems on Academic Procrastination in Adolescents: Emotion Regulation as Mediator - Aisha, Dinda; Dimala, Cempaka Putrie; Rahman, Puspa Rahayu Utami; Mora, Linda; Hakim, Arif Rahman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
In current society, academic procrastination has emerged as one of factors contributing to academic failure among youth. They often prioritize leisure activities over fulfilling academic responsibilities. The objective of this study is to examine the role of emotion regulation as a mediator in the relationship between internal problems, including non-suicidal self-injury (NSSI), paternal involvement, and dependent decision-making, on academic procrastination in adolescents in Karawang, West Java, Indonesia. This study used quantitative survey research design involving 148 adolescents who lived in Karawang as participants. The data collection technique was using 4 scales, there are The Self Harm Screening Inventory (SHSI), Brief Version Difficulties in Emotion Regulation Scale (DERS-18), Perception of Father Involvement Scale and General Decision-Making Style Questionnaire (GDMS). Research data analyzes by using JASP 0.19.1, an open-source program for statistical analysis. The results demonstrate that the relationship between NSSI and academic procrastination, father engagement and academic procrastination, and dependent decision making and academic procrastination may all be mediated by emotion regulation. Research finding indicates the potential of emotion regulation to function as a mediator in the relationship between variables and academic procrastination. Specifically, NSSI affects academic procrastination through emotion regulation as a mediator. Similarly, father involvement influences academic procrastination when emotion regulation is considered as a mediator. Lastly, dependent decision-making impacts academic procrastination if emotion regulation serves as a mediator. In conclusion, this research contributed to showed the importance of emotion regulation in explaining the reason behind academic procrastination. Especially for vulnerable youth who have less father involvement or have performed NSSI. They may not perform academic procrastination if they have high emotion regulation.